The structure of the terminal arborizations of physiologically identified retinal ganglion cell Y axons in the kitten. - Friedlander, M J (1985)
Retinal ganglion cell (r.g.c.) axons (n = 17) in the optic tract of 4-5 week-old kittens and adult cats (n = 4, this study, n = 27 from other reports) were studied both physiologically and morphologically. Axons were initially classified during extracellular recording with a battery of physiological tests that included Fourier analysis of the response to a sinusoidally counterphased sine-wave grating. Y axons had a significant second harmonic response component (greater than twice the fundamental) present independent of the spatial phase position of the grating. These axons were then recorded from intracellularly and subsequently filled ionophoretically with horseradish peroxidase (HRP). The HRP filled the axons' terminal arborizations in the dorsal lateral geniculate nucleus (l.g.n.). The innervation pattern and and structure of the terminal arborizations of the kitten r.g.c. Y axons were compared to those of the adult. The kitten Y axons innervated the l.g.n. in a pattern similar to that of the adult (individual branches from a single axon always innervated lamina A or A1 and may also have innervated lamina C, the medial interlaminar nucleus (m.i.n.) and/or sent branches that coursed medial to the l.g.n.). Fourteen of seventeen of these Y axons in the kitten innervated either of the A-laminae heavily (greater than 200 terminal boutons per axon). The remaining three r.g.c. Y axons in the kitten had only small arborizations within lamina A (less than fifty terminal boutons per axon) but heavily innervated lamina C. The structure of the terminal boutons on the kitten r.g.c. Y axons was highly variable when compared to axons of adult cats. Some of the boutons were spherical or crenulated as in the adult. Many others had filopodia and growth cone-like terminals with fine extensions. This variable maturation of terminal boutons was seen both between axons and on individual axons. The number of boutons on the kitten r.g.c. Y axons in the A-laminae was significantly less than that of adult Y axons. The mean numbers of boutons per axon were 476 and 1553 in the kittens and adult cats, respectively (P less than 0.001, Mann-Whitney U test). The width of the terminal arborization of individual Y axons in the A-laminae of the kittens was considerably smaller than in adult cats (mean widths of the terminal arborizations are 192 and 293 micron in the kittens and adult cats, respectively).(ABSTRACT TRUNCATED AT 400 WORDS)